Critical success factors of public private partnership (PPP)implementation in Malaysia - Ismail, Suhaiza; Ajija, Shochrul Rohmatul (2011)
Public Private Partnership (PPP) or Private Finance Initiative (PFI) is an increasingly popular choice for policymakers in implementing important public projects. PPP was officially announced in Malaysia in 2006 under the Ninth Malaysia Plan. Since then, many government projects were delivered via PPP. To ensure the ultimate objectives of PPP/PFI, identifying the critical success factors (CSFs) of PPP implementation is crucial.There are three objectives of this study. First, it aims to examine the importance of the CSFs as perceived by the overall respondents. Second, it intends to identify the differences concerning the importance of the CSFs between the public and private sectors. Third, it compares the importance of the top CSFs for PPP implementation in Malaysia with three other countries that have adopted PPP. A questionnaire survey was used to elicit the perceptions of public and private sectors on the key CSFs of PPP project in Malaysia. In total, 179 usable responses were analysed using SPSS to rank the importance of the CSFs and to examine the differences in the perceptions between the government and the private sector. Evidence obtained from prior studies on the CSFs of Hong Kong, Australia and Malaysia was compared to the top CSFs for PPP in Malaysia. The results show that good governance, commitment of the public and private sectors, favourable legal framework, sound economic policy and availability of finance market are the top five CSFs of PPP implementation in Malaysia. Although the rankings of many factors were different between the public and private sectors, there were no significant differences in the perception of the public and private sectors concerning the importance of the CSFs except for a few factors. There were mixed results concerning the comparison of CSFs between Malaysia and three other countries.